IMPLEMENTING RELIGIOUS MODERATION THROUGH A CONTEXTUAL CURRICULUM AT RIYADLUS SHOLIHIN ISLAMIC ELEMENTARY SCHOOL, WONOASIH, PROBOLINGGO - Fredi, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Religious moderation is an important thing that must be present in every element  of  human  life,  including  in  every  educational  process.  Because along with the ongoing process of human life, it will always be colored by social problems if it is not prevented with a character of loration through strengthening moderation, and until now, violence is still often found in the name of religion to discriminate against minority groups. This article aims to discuss the formulation of the concept of religious moderation in the context of Islamic perspective education. The hope is that it can be a reference in realizing the principle of moderation in education and as a study that supports the creation of moderation in Indonesia. The research method  used  is  a  literature  study  and  its  references  are  obtained  from sources in the library or other media related to the discussion. The results of  this  study  are  the  discovery  of  4  aspects  of  moderation  in  amaliyah, namely  Moderation  in  aqidah  (Belief).  Ubudiyah  (Worship).  Morals (Ethics).  And  Sharia  (Tasyri').  In  education,  4  discussions  of  religious moderation were found, namely first, in the subject matter, second, in the learning  process,  third,  in  learning  assessment,  fourth,  in  learning evaluation.